The Proceedings of the 24th Pediatric Work Physiology Meeting (Children and Exercise XXIV, 2009)
Children and Exercise XXIV presents the latest scientific research into paediatric exercise physiology, endocrinology, kinanthropometry, growth and maturation, and youth sport. Including contributions from a wide-range of leading international experts, the book is arranged into six thematic sections addressing: